American employers' interests and migrant labour in historical perspective - Marek Okólski (University of Warsaw, Centre of Migration Research (CMR), 2023)
The paper is the result of a larger effort to identify in contemporary history the links between employer interests and labour migration and the allocation of migrants in the labour market. The author focuses on the specifics of these relationships in the United States, under different political and economic conditions. In particular, he addresses conditions that prevailed during the early period of colonisation and settlement in North America, during the development and flourishing of the plantation economy, during the phase of intensive industrialisation and in the current period of globalisation. He discusses the ways in which employer interests related to the influx and employment of immigrants are expressed, including lobbying. The analysis contained in the paper demonstrates the persistence of employers interests related to migrant labour, despite changing political and economic circumstances.
Keywords: 330; labour migration; employer interests; United States